Transmission dynamics of COVID-19 outbreak in India and effectiveness of self-quarantine: a phase-wise data driven analysis. (15th January 2022) - Khan, Sahil; Khan, Md. Wasim; Kumar, Narender; Dohare, Ravins; Sankhwar, Shweta
The novel coronavirus disease referred to as COVID-19 was declared as pandemic by World Health Organisation (WHO). During this pandemic more than 988, 172 lives were lost and 7, 506, 090 approximately active cases were found across the world by 25 September 2020. To predict the novel coronavirus transmission dynamics, the SQEIHDR mathematical model is proposed to predict the COVID-19 transmission dynamics in India. The model is an extension of basic SEIR mathematical model with additional compartments. These additional compartments include self-quarantine (Q), isolation (H) and deceased (D) which helps to understand COVID-19 outbreak in India in more realistic way and supposed to suppress the rise of transmission. The SQEIHDR model's simulation covers ten phases (Phases 0 to 9) with different COVID-19 preparedness and response plans. The simulation results show significant changes in curve of infected population based on variation in compartment Q, which reveals efficacy of imposed as well as proposed preparedness and response plan. Aftermath with different conditions of preparedness and response plan highlight the keys for outbreak downfall i.e., rate of self-quarantine (Q) which includes general awareness, social distancing and food availability.